India : Private Health Services for the Poor - Radwan, Ismail (World Bank, Washington, DC, 2013)
Despite India's great strides since independence, fertility, mortality, and morbidity remain unacceptably high. Although poverty and low levels of education are the root causes of poor health outcomes, poor stewardship over the health system bears some responsibility. Although India's states exhibit a wide variation in health outcomes, all but the best-performing states need to focus on improving both sexual and reproductive health care and child health care, and on reducing communicable diseases for the poor. This paper examines the public and private responses to this situation detailing the reasons behind the failure of the public sector and ways in which the private sector can be encouraged to play a role in providing health care for the poor in India. The paper concludes that there are three promising areas for the private sector including; (i) contracting out the primary health centers, (ii) social franchising and (iii) demand-led financing. The study is focused on what to do to improve health care for the poor, while a series of separate background papers focus on how to do it, and state specific issues in Andhra Pradesh, Bihar, Karnataka, and Punjab.